2011
DOI: 10.1002/ange.201101869
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von Withanolid A, Untersuchung der neuritogenen Eigenschaften und Studien zur Sekretase‐Inhibierung

Abstract: Nervenzellen‐Doping: In einer stereoselektiven Synthese des Steroidlactons Withanolid A dienen eine En‐Reaktion mit Singulett‐Sauerstoff, eine Wharton‐Fragmentierung, eine Corey‐Seebach‐Homologisierung und eine vinyloge Aldolreaktion als Schlüsselschritte. Biologische Untersuchungen demonstrieren Neuritenwachstum, was die potenziell neuroaktive Wirkung dieses Naturstoffs in der traditionellen indischen Medizin stützt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2012
2012
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
(22 reference statements)
0
2
0
3
Order By: Relevance
“…The organic layer was washed with 1 N HCl (5 mL Â 3), saturated NaHCO 3 (5 mL Â 3), saturated NaCl (5 mL), dried over Na 2 SO 4 , filtered and concentrated. The residue was purified by silica gel column chromatography (petroleum ether-EtOAc, 7 : 1 to 5 : 1) affording a colorless oil of 20 (190 mg, 98%): [a] 23 D À16.2 (c 1.51, CHCl 3 ); R f = 0.52 (petroleum ether-EtOAc, 5 : 1); 1 (21). To a solution of 20 (100 mg, 0.12 mmol) in MeOH (5 mL) was added AcCl (50 mL) at 0 1C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The organic layer was washed with 1 N HCl (5 mL Â 3), saturated NaHCO 3 (5 mL Â 3), saturated NaCl (5 mL), dried over Na 2 SO 4 , filtered and concentrated. The residue was purified by silica gel column chromatography (petroleum ether-EtOAc, 7 : 1 to 5 : 1) affording a colorless oil of 20 (190 mg, 98%): [a] 23 D À16.2 (c 1.51, CHCl 3 ); R f = 0.52 (petroleum ether-EtOAc, 5 : 1); 1 (21). To a solution of 20 (100 mg, 0.12 mmol) in MeOH (5 mL) was added AcCl (50 mL) at 0 1C.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15] Recently, exogenous nonpeptidyl small molecules that could promote neurite outgrowth by inducing the activity of or showing a synergistic effect with neurotrophins, might be substituted for clinical use as promising neurotropic agents to treat fast growing neurodegenerative diseases. [16][17][18][19][20][21][22][23] Linckoside B (1) (Fig. 1), a new neuritogenic steroid glycoside, which was isolated from the Okinawan starfish Linckia laevigata by Qi et al, has demonstrated significant synergistic effects on the NGF-induced neuronal differentiation of PC12 cells that a 5% neuronal differentiation induced by NGF (2.5 ng mL À1 ) was enhanced to 87% in the presence of 1 (40 mM).…”
Section: Introductionmentioning
confidence: 99%
“…Die aus Meeresschwämmen der Gattungen Haliclona und Pellina isolierte Familie der Manzamine besteht aus verschiedenen strukturell komplexen Indolalkaloiden, [182] von denen Manzamin A (195) [183] ein breites biologisches Aktivitätsspektrum aufweist; unter anderem wirkt es gegen Krebs, Malaria, Bakterien und HIV und hat insektizide und entzündungshemmende Eigenschaften. [184] Darüber hinaus wirken die Manzamine A (195), E (197) und F (198) dung 11). [185] Zudem wurde für 195 der gleiche Wirkmechanismus vorgeschlagen wie für Lactacystin (1).…”
Section: Manzamin-alkaloideunclassified
“…[196] Gademann et al entwickelten eine Synthese von (+)-218 aus Pregnenolon (224; Schema 36). [197] Zu den wichtigen Reaktionen dieser Synthese gehçren a) eine vinyloge Aldolreaktion des Aldehyds 225 mit dem Lithiumenolat von 226 zum Lacton 227 und b) eine elegante Singulettsauerstoff-Enreaktion, [198] die den tertiären C5-Alkohol in 228 liefert. Der Singulettsauerstoff wurde in situ aus Sauerstoff durch Bestrahlen mit einer Na-Lampe in Gegenwart von meso-Tetraphenylporphyrin als Sensibilisator generiert.…”
Section: Steroideunclassified
See 1 more Smart Citation